K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

6 tháng 7 2016

a/ 3x(12x-4)-9x(4x-3)

=36x2-12x-36x2+27x

=(36x2-36x2)-12x+27x

=15x

b/ x(5-2x)+2x(x-1)

=5x-2x2+2x2-2x

=(5x-2x)-(-2x2+2x2)

=3x

c/ 5x(12x+7)-3x(20x-5)

=60x2+35x-60x2+15x

=(60x2-60x2)+(35x+15x)\

=50x

d/ 3x(2x-7)+2x(5-3x)

=6x2-21x+10x-6x2

=(6x2-6x2)+(10x-21x)

=-11x

e/ đề sai hay sao ý ra số to lắm @@

a: Ta có \(x^3-4x^2+x-n⋮x-4\)

\(\Leftrightarrow x^2\left(x-4\right)+x-4+n+4⋮x-4\)

=>n+4=0

hay n=-4

b: ta có: \(4x^3-2x^2+2x+n⋮2x+1\)

\(\Leftrightarrow4x^3+2x^2-4x^2-2x+4x+2+n-2⋮2x+1\)

=>n-2=0

hay n=2

c: \(\Leftrightarrow x^4-3x^3+3x^3-9x^2+6x^2-18x+21x-63-n+63⋮x-3\)

=>63-n=0

hay n=63

30 tháng 10 2023

a: ĐKXD: x<>0

\(\dfrac{14x^3+12x^2-14x}{2x}=\left(x+2\right)\left(3x-4\right)\)

=>\(\dfrac{2x\left(7x^2+6x-7\right)}{2x}=\left(x+2\right)\left(3x-4\right)\)

=>\(7x^2+6x-7=3x^2-4x+6x-8\)

=>\(7x^2+6x-7=3x^2+2x-8\)

=>\(4x^2+4x+1=0\)

=>\(\left(2x+1\right)^2=0\)

=>2x+1=0

=>x=-1/2(nhận)

b: \(\left(4x-5\right)\left(6x+1\right)-\left(8x+3\right)\left(3x-4\right)=15\)

=>\(24x^2+4x-30x-5-\left(24x^2-32x+9x-12\right)=15\)

=>\(24x^2-26x-5-24x^2+23x+12=15\)

=>-3x+7=15

=>-3x=8

=>\(x=-\dfrac{8}{3}\)

17 tháng 6 2018

a/ \(\left(12x-5\right)\left(4x-1\right)+\left(3x-7\right)\left(1-16x\right)=81\)

<=> \(48x^2-12x-20x+5+3x-48x^2-7+112x=81\)

<=> \(83x-2=81\)

<=> \(83x=83\)

<=> \(x=1\)

b/ \(\left(2x-3\right)\left(2x+3\right)-\left(4x+1\right)x=1\)

<=> \(4x^2-9-4x^2-x=1\)

<=> \(-\left(9+x\right)=1\)

<=> \(9+x=-1\)

<=> \(x=-10\)

c/ \(3x^2-\left(x+2\right)\left(3x-1\right)=-7\)

<=> \(3x^2-\left(3x^2-x+6x-2\right)=-7\)

<=> \(3x^2-3x^2+x-6x+2=-7\)

<=> \(-5x+2=-7\)

<=> \(-5x=-9\)

<=> \(x=\frac{9}{5}\)

1: \(\Leftrightarrow-4x^2+3x-4x^2+8x=10\)

=>-8x^2+11x-10=0

=>\(x\in\varnothing\)

2: \(\Leftrightarrow5x^2-15x+5+x-5x^2=x-2\)

=>-14x+5=x-2

=>-15x=-7

=>x=7/15

3: \(\Leftrightarrow12x^2-12x^2+20x=10x-17\)

=>10x=-17

=>x=-17/10

4: \(\Leftrightarrow4x^2-2x+3-4x^2+20x=7x-3\)

=>18x+3=7x-3

=>11x=-6

=>x=-6/11

5: \(\Leftrightarrow-3x+15+5x-5+3x^2=4-x\)

\(\Leftrightarrow3x^2+2x+10-4+x=0\)

=>3x^2+3x+6=0

hay \(x\in\varnothing\)